Diaspora groups and development in fragile situations: Lessons learnt - Nauja Kleist; Ida Vammen (Danish Institute for International Studies (DIIS), 2012)
This report examines programmes targeting specific migrants and diaspora groups as development agents with particular emphasis on fragile situations. It is part of the Research and Communication Programme (ReCom) on Foreign Aid, and is commissioned by the Danish Ministry of Foreign Affairs. The examination has the following objectives: 1. To study the results of migration-development programmes with particular emphasis on improved poverty reduction and service delivery, and reconstruction processes. 2. To identify practices producing intended or unintended positive and negative results as well as any dilemmas in these results, and to relate practices producing desired results across contexts. 3. To assess the validity and scope of the material on diaspora groups as development agents in fragile situations. Three kinds of programmes are examined respectively focusing on: remittances, diaspora organisations and return, together representing some of the most common migration-development programmes in fragile situations. Selection criteria for specific programmes and cases were based on relevance and good documentation. This material is supplemented by interviews with Danish NGO personnel, a Somali diaspora organisation, and academic studies. The study shows that programme experiences are mixed and highly contextual. Nevertheless, some general lessons learnt have been identified, presented below.
Keywords: 300